Місцеві податки та збори в Україні: об’єкт чи предмет податкових правовідносин? - Вікторчук, М. В.; Viktorchuk, M. V. (Право і безпека. - 2014. - № 4 (55). - С. 178-182, 2014)
Досліджено місце місцевих податків та зборів у структурі податкових правовідносин. Розглянуто наявні теоретичні підходи до розуміння об’єктів та предметів податкових правовідносин на етапі становлення податкового права. Визначено особливості місцевих податків та зборів як об’єкта та предмета податкових правовідносин.

Figuring place of local taxes in the tax legal structure is essential for science tax law and further improvement of tax legislation. The article deals with role of local taxes and fees in the structure of tax relations. The purpose of the article is to study the theoretical approaches to determine the structure of tax relations, place of local taxes and fees in this structure, with further substantiation of the optimal value of the object and the subject of tax relations. The methodological basis of the article is a set of general and specific methods. Comparative legal method allowed us to explore the place of local taxes and fees in the structure of tax relations. The article describes the scientific approaches to the definition of relations in general, and in particular tax. The author studies current theoretical issues of approaches to understanding objects and subject of tax legal relations at the stage of creating tax law. The article analyzed scholars positions on the interpretation of the category «object of relationhips» and formed the definition of the relevant concepts concerning the relationship of the field of taxation. Аscertained by the peculiarities of local taxes and fees as object and subject of tax legal relations. The author concludes that the ownership of local taxes and fees to the subject and object of tax relations.

Исследовано место местных налогов и сборов в структуре налоговых правоотношений. Рассмотрены существующие теоретические подходы к пониманию объектов и предметов налоговых правоотношений на этапе становления налогового права. Определены особенности местных налогов и сборов как объекта и предмета налоговых правоотношений.
Local taxes and fees in ukraine: the object or subject of tax legal relations?
Местные налоги и сборы в Украине: объект или предмет налоговых правоотношений?
Keywords: місцеві податки та збори; local taxes and fees; местные налоги и сборы; податкові правовідносини; tax legal relations; налоговые правоотношения; структура податкових правовідносин; tructure of tax relations; структура налоговых правоотношений; об’єкт податкових правовідносин; object of tax relations; объект налогового правоотношения; предмет податкових правовідносин; subject of tax relations; предмет налогового правоотношения